Let #(x)/(y)# represent the fraction

The problem specifies

#(a)# Adding #1# to the numerator and denominator makes the fraction equal to #(1)/(2)#

#(b)# Subtracting #1# from the top and bottom makes the fraction equal to #(1)/(3)#

#(a) (x + 1)/(y+1) = (1)/(2)#

#(b) (x - 1)/(y-1) = (1)/(3)#

#color(white)(........................)#**―――――――**

**Solve for #x#, already defined as "the numerator of the original equation"**

These equations can be solved as Ratio&Proportion problems.

#1)# Cross multiply both equations

#(a)# #2(x+1)=1(y+1)#

#(b)# #3(x−1)=1(y−1)#

#2)# Clear the parentheses

#(a)# #2x + 2 = y + 1#

#(b)# #3x - 3 = y - 1#

#3)# Write the equations with the variables on the left and the numbers on the right

#(a)# #2x - y =# - #1#

#(b)# #3x - y = 2#

#4)# Start with Equation #(b)# and subtract Equation #(a)#

(Do it in this order to avoid negative numbers.)

#(b)# #3x - y = 2#

#(a)# - (#2x - y =# - #1#)

#5)# Clear the parentheses and combine to eliminate the #y# term

#(b)# #3x - y = 2#

#(a)# #-2x + y = 1#

―――――――――

#color(white)(..........) x# #color(white)(...m)= 3# #larr# already defined as "the numerator of the original fraction"

#color(white)(........................)#**―――――――**

**Solve for #y#, already defined as "the denominator of the original fraction"**

#1)# Using one of the original equations, sub in #3# in the place of #x#

#(color(blue)(x) - 1)/(y-1) = (1)/(3)#

#(color(blue)(3) - 1)/(y-1) = (1)/(3)#

#2)# Cross multiply and solve for #y#, already defined as "the denominator of the original fraction"

#3(3-1)=1(y-1)#

#3)# Solve inside the parentheses

#3(2)=1(y-1)#

#4)# Clear the parentheses by distributing the #3# and the #1#

#6 = y - 1#

#5)# Add #1# to both sides to isolate #y#

#6)# #7 = y# #larr# answer for #y#, defined as "the denominator of the original fraction"

#"Answer"#

The original fraction is #(3)/(7)#

#color(white)(........................)#**―――――――**

**Check**

Add #1# to the top and bottom of #(3)/(7)# to see if it becomes #(1)/(2)#

#(3 + 1)/(7+1) =# #(4)/(8) = (1)/(2)# ✓

Subtract #1# from the top and bottom to see if it becomes #(1)/(3)#

#(3-1)/(7-1) =# #(2)/(6) = (1)/(3)# ✓

#Check#